Evaluasi Pembelajaran Sebagai Sebuah Studi Literatur - Fuadiy, Moch. Rizal (DIMAR: Jurnal Pendidikan Islam, 2021)
This article discusses learning evaluation based on a literature study. Learning evaluation is a systematic process of collecting, analyzing, and interpreting data regarding students' learning achievements. Experts such as Thomas M. Haladyna, Dale H. Schunk, Airasian, R.L. Linn, N.E. Gronland, Mulyasa, and Hamalik emphasize the importance of collecting objective data and conducting in-depth analysis in learning evaluation. The results of evaluation are used for learning improvement and decision-making that impact student progress. The goals of learning evaluation are to obtain accurate information about students' achievement of learning objectives, measure students' understanding, skills, and mastery of the learning material, evaluate students' achievements, gather information about the effectiveness of the learning process, and identify students' needs and weaknesses. The process of learning evaluation involves steps such as identifying evaluation objectives, developing evaluation instruments, collecting evaluation data, analyzing and interpreting the data, providing feedback to students and teachers, and using the evaluation results for learning improvement and better decision-making. The results of learning evaluation include information about individual students' progress, students' success in mastering concepts and skills, assessment of students' progress in achieving learning objectives, the effectiveness of learning methods and strategies, students' competency achievements, students' success in applying knowledge and skills, and students' understanding of the learning material. Overall, learning evaluation plays a crucial role in understanding students' development, improving the quality of learning, identifying students' needs, adjusting learning strategies, and achieving learning objectives optimally. A systematic and planned learning evaluation process provides relevant information that can be used for improvement and adjustments in the learning process.